Atrioventricular nodal echoes over a wide echo window as a therapeutic end point for the catheter-guided radiofrequency ablation of atrioventricular nodal reentrant tachycardia: a prospective study. Issue 4 (15th March 2017) - Nikoo, Mohammad Hossein; Attar, Armin; Pourmontaseri, Mohammad; Jorat, Mohammad Vahid; Kafi, Mohammad
Abstract: Aims: In previous retrospective studies, it was shown that the presence of residual single atrioventricular node (AVN) echoes with an echo zone longer than 30 ms may increase the rate of recurrence after radiofrequency ablation (RFA) of slow pathway in patients with AVN reentrant tachycardia (AVNRT). Based on that, some centres perform additional RFA in these patients. However, this opinion has never been tested prospectively and many centres do not perform re-ablation in these patients. The purpose of this study was to test whether persistence of a single AVN echo over a wide echo zone is a valid end point for RFA. Methods and results: In this prospective study, 576 patients who had a non-inducible arrhythmia post-RFA of AVNRT were divided into those with a remnant echo over a wide echo zone (case group) and those reaching classical end points (control group). The primary end point of the study was recurrence and patients were followed for 34.5 ± 18.8 months. In the control group ( n  = 510), 14 patients (2.7%) had a recurrence while no recurrence was seen in the case group ( n  = 66) (final cure rate, 97.3 vs. 100%; difference, 2.7%; upper bound of the 98% CI, 0.0488; P  < 0.0001 for non-inferiority). Two complete heart blocks (0.4%) happened in the control group and none in the case group ( P  = 0.784). Conclusion: Non-inducibility in the presence of a wide echo window is non-inferior to non-inducibility in the presence of narrow echo window or no AVN echoes. In general, the presence of a single echo beat is not an indication for further ablation and this applies for both narrow and wide windows.